Nanometer-scale separation of d10 Zn2+-layers and twin–shift competition in Ba8ZnNb6O24-based 8-layered hexagonal perovskites1. Issue 29 (7th August 2015) - Lu, Fengqi; Wang, Xiaoming; Pan, Zhengwei; Pan, Fengjuan; Chai, Shiqiang; Liang, Chaolun; Wang, Quanchao; Wang, Jing; Fang, Liang; Kuang, Xiaojun; Jing, Xiping
<x xml:space="preserve">Abstract</x> The shifted hexagonal perovskite Ba8ZnNb6O24 demonstrates ∼ 1.9 nm separation of octahedral d10 Zn2+-layers and twin–shift competition upon Sb5+/Ta5+ substitution for Nb5+.